2013
DOI: 10.1371/journal.pone.0056209
|View full text |Cite
|
Sign up to set email alerts
|

Foxp3+ Treg Expanded from Patients with Established Diabetes Reduce Helios Expression while Retaining Normal Function Compared to Healthy Individuals

Abstract: Foxp3+ regulatory T cells (Treg) play a crucial role in regulating immune tolerance. The use of Treg to restore immune tolerance is considered an attractive novel approach to inhibit autoimmune disease, including type 1 diabetes (T1D), and to prevent rejection of organ transplants. In view of the goal of developing autologous Treg-based cell therapy for patients with long-term (>15 years) T1D, it will be necessary to expand a sufficient amount of functional Treg in vitro in order to study and compare Treg from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 43 publications
3
12
0
Order By: Relevance
“…IFN-g-producing Foxp3+ cells, or so-called Th1-like cells, can be polarized in vitro from conventional Treg upon the sequential exposure to IFN-g and then to IL-12, as demonstrated in the mouse system [36] and as we have confirmed using human Treg [9]. Th1-like Treg have been observed in a variety of inflammatory settings dominated by type-1 responses, such as graft-versus-host disease [37], viral infection [38], parasite infection [39], MS [40] and diabetes [41,42]. We have recently described that Th1-like Treg accumulate in the inflamed liver tissue of patients with chronic HCV infection, in line with the local abundance of IL-12 and IFN-g.…”
Section: Impact Of Type-i Ifns On Other Cd4+ Regulatory Subsetssupporting
confidence: 72%
“…IFN-g-producing Foxp3+ cells, or so-called Th1-like cells, can be polarized in vitro from conventional Treg upon the sequential exposure to IFN-g and then to IL-12, as demonstrated in the mouse system [36] and as we have confirmed using human Treg [9]. Th1-like Treg have been observed in a variety of inflammatory settings dominated by type-1 responses, such as graft-versus-host disease [37], viral infection [38], parasite infection [39], MS [40] and diabetes [41,42]. We have recently described that Th1-like Treg accumulate in the inflamed liver tissue of patients with chronic HCV infection, in line with the local abundance of IL-12 and IFN-g.…”
Section: Impact Of Type-i Ifns On Other Cd4+ Regulatory Subsetssupporting
confidence: 72%
“…TIGIT + subset of Tregs have been shown to predominantly inhibit Th1 and Th17 cells without affecting Th2 cells40. Helios, an Ikoras transcription factor family member, has also been reported to be associated with Treg functions41 and suppression of autoimmune diabetes42. Increased expression of these suppressive markers in OX40L-JAG1 expanded Tregs could help sustain their suppressive functions.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of additional markers for delineating cells of T reg lineage, CD39 and CD45RA have been included as possible markers for detection of T reg cells. Thus far, it has been shown that T reg cells, defined as CD4 + FoxP3 + , express more CD45RO but less CD45RA in T1D patients compared to healthy controls . Also in fulminant T1D patients, the frequency of CD45RA − FoxP3 high activated T reg cells is shown to be significantly lower compared to patients with type 1A diabetes .…”
Section: Discussionmentioning
confidence: 99%